Wildlife responses to livestock guard dogs and domestic sheep on open range - Kinka, Daniel; Schultz, Jeffrey T.; Young, Julie K. (DigitalCommons@University of Nebraska - Lincoln, 2021)
Domestic sheep (Ovis aries) are an attractant to carnivores; however, sheep are often accompanied by humans and livestock guardian dogs (LGDs; Canis familiaris), which defend sheep from depredation. Sheep also compete directly with wildlife for grazing resources. Although practiced for millennia in much of the world outside North America, the effect that transhumance has on wildlife is poorly understood. To test the effect of sheep bands (sheep, humans, and LGDs) on wildlife, we modeled the detection probability of wild mammals relative to the presence of sheep bands in the Northwestern United States. Sheep band presence was associated with a reduction of about half in the likelihood of detecting large carnivores (Ursus americanus, Ursus arctos, Canis lupus, and Puma concolor, p < 0.05) and deer (Odocoileus spp., p < 0.01), both while the band was present and after it left the area. Contrastingly, coyotes (Canis latrans) were more than three times as likely to be detected when sheep bands were present (p < 0.001), and twice as likely after sheep bands left (p < 0.01). Coyotes were the only species we modeled that was more likely to be detected when a sheep band was present. It is unclear how long these effects persist after a sheep band has moved through an area, but our results suggest that transhumance temporarily displaces many large mammals, which results in mesopredator release of coyotes. This study suggests there is a tradeoff between the conservation benefits provided by LGDs and humans protecting sheep and the costs of displacement to some wild mammals.